THE ROLE OF ISLAMIC BROADCASTING IN SHAPING PUBLIC PERCEPTION: ETHICAL APPROACHES AND MODERN MEDIA INTEGRATION - Thoyib, M. Syarif (Berajah Journal, 2024)
Islamic broadcasting plays a crucial role in the dissemination of Islamic teachings and values, shaping the moral and ethical framework of Muslim communities worldwide. In today’s digital age, the landscape of Islamic communication has significantly evolved with the integration of modern media platforms such as television, radio, and social media. This paper explores the intersection between traditional Islamic broadcasting and modern media technologies, focusing on how these platforms influence the spread of Islamic messages and shape public perception. The study examines key ethical principles that guide Islamic broadcasting, including the importance of truthfulness, respect, and community welfare. Through an analysis of case studies from prominent Islamic media networks, the paper highlights how digital tools such as social media, podcasts, and online streaming have revolutionized Islamic broadcasting, making it more accessible to a global audience. Additionally, the research delves into the challenges that arise from the widespread use of modern media, including the risk of misinformation, ethical dilemmas in content creation, and the impact of commercialization on the authenticity of religious communication. The findings suggest that while modern media platforms offer new opportunities for the dissemination of Islamic teachings, there is a pressing need for greater ethical oversight to ensure that the integrity of the message is preserved.